Statement by the Managing Director on the Independent Evaluation Office Report on Recurring Issues from a Decade of Evaluation : Lessons for the IMF. (Policy Papers; Policy Paper ;, 2014)
The Managing Director welcomes the IEO's novel report, which identifies recurring issues from past evaluations and assesses progress in addressing them. The report's focus on organizational silos, attention to risks and uncertainty, country and institutional context, evenhandedness, and Executive Board guidance and oversight is appropriate given their relevance and importance for the effectiveness and credibility of IMF operations.